Spectral downshift of Three-wave system and Bichromatic waves under “sea ice” - Sato, Koya; Waseda, Takuji; Kodaira, Tsubasa; Fujiwara, Yasushi; Nose, Takehiko; Katsuno, Tomotaka (2023)
The 14th Symposium on Polar Science/Interdisciplinary sessions [IA] Arctic Research, Thu. 16 Nov. / 2F Auditorium, National Institute of Polar Research conference object